Southward expansion of the Chilean salmon industry in the Patagonian Fjords: main environmental challenges. (24th March 2013) - Niklitschek, Edwin J.; Soto, Doris; Lafon, Alejandra; Molinet, Carlos; Toledo, Pamela
Abstract Chile is the second largest producer of farmed salmon in the world. After reaching a peak harvest of 631 000 tonnes in 2008, a severe sanitary and production crisis triggered a major legal and operational reorganization, and an imminent expansion of the industry into the Aysén Fjords System (AFS). This expansion has caused increasing national and international concern about its potential negative impact upon this pristine area, which holds a mosaic of unique ecosystems and three World Biosphere Reserves. This paper reviews and provides some upper bounds to potential impacts under two feasible production scenarios. It is concluded that severe but highly localized mid‐term damage to the sea‐floor bottom may affect up to 6200 ha. Although this surface area represents only 0.5% of the AFS, the high heterogeneity and limited scientific knowledge of local ecosystems increase the risks of damaging sensitive habitats, communities or populations. While additional inputs of up to 60 000 t of nitrogen and 8000 t of phosphorus can be predicted, the estimation of carrying capacities is a pendant and urgent task to be accomplished in this area. If current escape rates are not reduced, the average number of escaped salmon may exceed 4.4 million individuals each year, able to consume up to 6600 t of pelagic prey from local ecosystems. We recommend following a strict precautionary approach, not granting new farming leases until sufficient information about the risk and magnitude of these impacts is obtained and transformed into effective management actions.